Excel VBA programming for dummies - Walkenbach, John. (Hoboken, N.J. : Wiley Pub., 2010)
" ... Open the book and find : how to work in the Visual Basic Editor ; tips for error-handling and bug extermination ; ways to build automatic procedures and events ; how to use Excel macro recorder ; UserForm technique and tricks ; instructions for designing VBA macros ; steps for accessing your macros through the user interface ; secrets for creating Excel add-ins ..."--Page 4 of cover.
pt. 1. Introducing VBA -- pt. 2. How VBA works with Excel -- pt. 3. Programming concepts -- pt. 4. Communicating with your users -- pt. 5. Putting it all together -- pt. 6. The part of tens.
Print version record.
English.
John Wiley and Sons
Keywords: Microsoft Visual Basic for applications; Microsoft Excel (Computer file); Microsoft Excel (Computer file); Microsoft Visual Basic for applications; Electronic spreadsheets; Computer software -- Development; Tableurs; COMPUTERS -- Desktop Applications -- Spreadsheets; Computer software -- Development; Electronic spreadsheets; 2; Excel 2007; Excel 2010; Excel (logiciel) -- Visual Basic (langage de programmation) -- manuel; 2; Datorprogram; Kalkylprogram; Datavetenskap